Prevalence of stress and urge urinary incontinence in elite athletes and controls - Bo, K.; Sundgot-Borgen, J. (Medicine & Science in Sports & Exercise, 2001)
. Purpose: The purposes of the present study were to examine the prevalence of stress and urge incontinence in female elite athletes and controls, assess a possible association between urge and stress incontinence and eating disorders, and assess a possible association between stress and urge incontinence and menstrual irregularity. Methods: This was a two-stage study including a screening part by questionnaire and a clinical interview. Questions included in the questionnaire were related to training history, menstrual history, eating behavior, and stress and urge incontinence. DSM-IV criteria were used in the clinical part of the study to diagnose eating disorders in those classified as being at risk. The total population of female elite athletes, defined as one representing the national team for junior or senior (N = 660), and age-matched nonathlete controls (N = 765) aged 15-39 were asked to answer the questionnaire. The response rate was 87% and 75% for athletes and controls, respectively. Results: Four percent of the athletes and 33% of the controls had delivered (P < 0.05). There was no significant difference in prevalence of stress urinary incontinence (SUI) in the athletes and controls, 41% and 39%, respectively. No significant difference was observed between sport groups. No difference in the frequency of urge incontinence was found when athletes (16%) and controls (19%) were compared. Twenty percent of the elite athletes and 9% of the controls met the DSM-IV criteria for eating disorder. The prevalence of SUI (49.5%) and urge incontinence (20%) in eating disordered athletes was significantly higher than in healthy athletes, 38.8% (P = 0.003) and 15% (P = 0.048). No difference in prevalence was observed when eating disordered nonathletes (39%) and healthy nonathletes (39%) were compared (P = 0.426). Conclusion: There is a high prevalence of stress and urge incontinence in female elite athletes. The frequency of SUI and urge incontinence was significantly higher in eating disordered athletes compared with healthy athletes.